2020
DOI: 10.1024/0300-9831/a000518
|View full text |Cite
|
Sign up to set email alerts
|

Boric acid and Borax Supplementation Reduces Weight Gain in Overweight Rats and Alter L-Carnitine and IGF-I Levels

Abstract: Abstract. The aim of this study was to investigate the effects of boric acid (BA) and borax (BX) on live weight and obesity associated molecules including leptin, L-carnitine, insulin-like growth factor 1 (IGF-I), and heat shock proteins 70 (HSP70) in rats fed with high-fat diet. A total of 60 rats were equally allocated as ND (normal diet), HF (high-fat diet), HF+BA, HF+BX, ND+BX, ND+BA. Body weight increases in HF+BA (85 g) and HF+BX (86 g) were significantly lower (p<0.05) compared to HF group (126 g). B… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 44 publications
0
5
0
Order By: Relevance
“…This situation is compatible with studies conducted by adding boron to the diet of rats and drinking water of rats, with studies in which the body weights of the subjects decreased. [24][25][26] In this study, antioxidant defense mechanisms were increased boron-supplemented groups to prevent damage caused by free radicals in tissues that were produced because of high-fat content in the experimental diet. Antioxidant defense, which prevents radical production and scavenges the produced radicals, takes place in two structures enzymatic and nonenzymatic defense mechanisms.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This situation is compatible with studies conducted by adding boron to the diet of rats and drinking water of rats, with studies in which the body weights of the subjects decreased. [24][25][26] In this study, antioxidant defense mechanisms were increased boron-supplemented groups to prevent damage caused by free radicals in tissues that were produced because of high-fat content in the experimental diet. Antioxidant defense, which prevents radical production and scavenges the produced radicals, takes place in two structures enzymatic and nonenzymatic defense mechanisms.…”
Section: Discussionmentioning
confidence: 99%
“…This situation is compatible with studies conducted by adding boron to the diet of rats and drinking water of rats, with studies in which the body weights of the subjects decreased. [ 24–26 ]…”
Section: Discussionmentioning
confidence: 99%
“…50 In rats fed an HFD, it has been shown that increased boron intake reduces body weight by altering serum L-carnitine and insulin-like growth factor 1 levels. 51 In humans, it has been reported that high dietary boron intake increases serum and saliva boron levels and reduces body weight, serum low-density lipoprotein cholesterol, very-low-density lipoprotein cholesterol, total cholesterol, and triglyceride levels. 44…”
Section: Discussionmentioning
confidence: 99%
“…The effects of boron on antioxidant oxidative stress is one of the current controversial issues. In addition, the lowering effects of boron compounds on body weight are promising for the problems caused by excessive weight (Atakisi et al, 2019;Fail et al, 1998). Increased oxidative stress with increased weight gain leads to an increase in the amount of free radicals and deterioration of homeostasis between free radicals and antioxidants in the body against antioxidants.…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies have demonstrated that boric acid might be effective in decreasing body weight (Atakisi et al, 2019;Fail et al, 1998;Yildiz et al, 2013). A study reported that addition of various doses (1200, 2500, 5000, 10000, 20000 ppm) of boric acid to drinking water decreased body weight and this decrease was positively correlated with dosage (Fail et al, 1998).…”
Section: Sharma Et Al Reported That Boron Supplements Have Positive E...mentioning
confidence: 99%